Exploring of Jamu Pahitan, a Traditional Bitter Drink Originating from Java, Indonesia: Ethnopharmacological Studies and Scientific Evidence - Witoyo, Jatmiko Eko; Utoro, Panggulu Ahmad Ramadhani; Permatasari, Nelsy Dian; Maligan, Jaya Mahar (Journal of Food and Agricultural Product, 2025)
Jamu is a traditional Indonesian drink that has been recognized worldwide, and is usually drunk by Indonesians, especially Javanese, as a health drink. Jamu pahitan is a type of jamu that is made from one, two, or a mixture of herbal ingredients like Andrographis paniculata and Tinospora cordifolia, with or without adding other herbal ingredients. In Indonesia, jamu pahitan has long been used by local communities, particularly Javanese, as a blood purifier, an anti-allergy, and even a treatment for skin conditions. On another hand, Jamu pahitan could potentially be used to diabetes mellitus management, based on recent studies. Nevertheless, there are still few thorough and scientific investigations on the composition, processing, public health perception, and efficacy of jamu pahitan and its herbal constituents, particularly with regard to diabetes management. Therefore, the formula composition, processing, societal health perception, and pharmacological clinical evidence of jamu pahitan and its constituent herbal ingredients, particularly for the control of diabetes, are all covered in this review. This study's methodology was a narrative literature review, using 1992 - 2023 data as foundational information on the subjects covered. In vitro and in vivo investigations have demonstrated that the herbal ingredients contain a variety of bioactive chemicals, and the aqueous extract of the herbal ingredients composed of jamu pahitan and jamu pahitan alone has pharmacological action as antidiabetic agent. Keywords: anti-diabetic, bioactive compound, formula composition, jamu pahitan, traditional medicine